Organization of physical education of children and youth in the People’s republic of China - Цзін [Wang Jing], Ван; Бондар [Anastasiia Bondar], Анастасія Сергіївна (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> Purpose: exposure of features of organization of physical education in the People's Republic of China. They are three-level system of physical education was formed in China: prepares preschool establishments, schools, Institutes of higher. The programs include on physical education: health athletic, gymnastics, sports games, ushu, square-bashing, swimming, rolling on skates, sky, tourism, traditional ethnic sports. Obligatory employments on a physical culture are conducted twice in a week, 100% students visit these employments. 40,9% polled specialists of physical culture of China consider that a process of physical education is a process of athletic education, on their opinion, the office workers of type state administration (42,2%), scientists (25,8%) and teachers, must determine maintenance of physical education (32%). <!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->